Association between venous blood lactate levels and differences in quantitative capillary refill time. Issue 4 (5th June 2018) - Oi, Yasufumi; Sato, Kosuke; Nogaki, Ayako; Shinohara, Mafumi; Matsumoto, Jun; Abe, Takeru; Morimura, Naoto
Abstract : Aim: Capillary refill time has been widely adopted for clinical assessment of the circulatory status of patients in emergency settings. We previously introduced quantitative capillary refill time and found a positive association between longer quantitative capillary refill time and higher lactate levels in the intensive care units, but not in the emergency department. In this study, we aimed to identify a quantitative and clinically applicable index of circulatory status (Δ A b ) that can be measured with quantitative capillary refill time, then evaluated the linear association between this index and lactate levels in the emergency department. Methods: We undertook a prospective single‐center observational study at a university hospital from November 2015 to July 2016. We included 139 patients with endogenous diseases to test the association between quantitative capillary refill time, Δ A b (measured with a pulse oximeter), and lactate levels. Results: Δ A b was independently and significantly associated with high lactate levels (odds ratio [95% confidence interval]: 0.16 [0.05–0.45]). Conclusions: We introduced Δ A b, measured using quantitative capillary refill time, as a surrogate index of lactate levels to overcome the shortcomings of capillary refill time. We showed that Δ A b is a feasible, non‐invasive, and rapid assessment of patients with high lactate levels in emergency primary care settings. Future multicenter studies with a longitudinal design should be undertaken to verify our findings. Abstract : We introduced Δ A b, measured using quantitative capillary refill time, as a surrogate index of lactate levels to overcome the shortcomings of capillary refill time. We showed that Δ A b is a feasible, non‐invasive, and rapid assessment of patients with high lactate levels in emergency primary care settings.